Off Pump Complete Revascularization Through Left Lateral Thoracotomy (ThoraCAB): NICVD Experience (Cardiovascular Journal, 2010)
Background: Conventional coronary artery bypass surgery (CABG) is associated with substantial morbidity caused by cardiopulmonary bypass (CPB) and median sternotomy. Here we described an innovative technique to perform complete revascularization through a left lateral thoracotomy without CPB (ThoraCAB). Methods: From September 2005 to December 2008 a total 83 patients underwent ThoraCAB in National Institute of Cardio Vascular Diseases (NICVD). The patient is positioned with the left side elevated to 45 degree. A 6 to 8 inches long incision is made over the left 4th or 5th intercostal space from just medial to the nipple to the anterior axillary line. The left internal mammary artery (LIMA) is harvested as a pedicle graft under vision. Distal coronary anastomosis is completed first on the beating heart using a stabilizer, followed by proximal anastomoses on the descending aorta. Peroperative and postoperative complication the arrhythmia hypotension wound infection death was observed. Results: Complete revascularization was achieved in all patients. The number of grafts averaged 2.18±1.08 per patients. One patient died (1.2%) due to severe respiratory acidosis. One patient (1.2%) was converted to CPB due to arrhythmia. No strokes were observed. Of these patients, 7.2% developed new onset postoperative atrial fibrillation. Conclusion: ThoraCAB has been feasible in the vast majority of the patients requiring CABG surgery. The prevalence of the post operative atrial fibrillation was low. Left lateral thoracotomy offers an attractive and effective alteration to Off Pump median sternotomy. Key words: ThoraCAB; Lateral thoracotomy; CABG DOI: 10.3329/cardio.v3i1.6424Cardiovasc. j. 2010; 3(1): 33-36